Search for the great apes [videorecording] - Kane, Dennis B.; Saxon, David; Wiser, Christine; Young, Rober M.; National Geographic Society; Wolfer Production ([Washington, D.C.] The Society, 1975)
Features the fieldwork of scientists, David Fossey and Birute Galdikas-Brindamour on the mountain gorilla and orangutan in the mountains of Central Africa and within the rain forest of Indonesian Borneo.
VHS.
Narrated by John Kiley ; written by Budwiser ; edited by David Saxon.
Keywords: Gorilla -- Behavior; Gorilla; Orangutan -- Behavior. -- Borneo; Orangutan